(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2019)
Silvio Soldini’s documentaries, like many of his feature films, focus on the representations of marginalized groups, on the unveiling of non-mainstream Italian realities and on the interweaving of multiple narratives that resist resolution. In this article, I consider three of Soldini’s more recent documentaries, “Per altri occhi”, “Tre Milano”, and “Il fiume ha sempre ragione”, focusing particularly on how Soldini engages us in a form of active viewing that draws attention not just to the visual but to other senses, eliciting affective response and providing space for reflection on ways of being in the world.